THE INFLUENCE OF JOB CHARACTERISTICS AND JOB PLACEMENT ON PERFORMANCE FINANCE OFFICER AT THE HIGHWAY AND CONSTRUCTION AGENCY LAMPUNG PROVINCE - Dina Sabila; Iskandar Ali Alam (ZILLZELL MEDIA PRIMA, 2024)
The importance of job characteristics and job placement affects the performance of financial employees. The purpose of this study is to find out whether the variables of job characteristics, job placement, affect the performance of financial employees of the BMBK Office of Lampung Province. The sample in this study is 35 respondents in the Finance section of the BMBK Office, using multiple linear regression analysis, and validity test methods, reality tests with descriptive analysis, by using the (SPSS)23 program as a tool to analyze data through statistical analysis. After conducting research by filling out a questionnaire, the results were obtained that 30 respondents (85.7%) agreed with the characteristics of the job, for the variable of employing work, 21 respondents (60.0%) expressed their agreement, for the variable of employee performance, as many as 25 respondents (71.5%) expressed agreement. The findings of this study show that characteristics and placement have a significant and positive influence on the performance of BMBK Service Employees partially. Simultaneously, the characteristic variables and placement together have a significant effect and contribute 90.6% of the relationships between the variables studied by the researchers.